Stat3 Activation in Murine Colitis Induced by Enterotoxigenic Bacteroides fragilis. Issue 5 (3rd April 2014) - Wick, Elizabeth C.; Rabizadeh, Shervin; Albesiano, Emilia; Wu, XinQun; Wu, Shaoguang; Chan, June; Rhee, Ki-Jong; Ortega, Guillermo; Huso, David L.; Pardoll, Drew; Housseau, Franck; Sears, Cynthia L.
Abstract : Background: Enterotoxigenic Bacteroides fragilis (ETBF), a molecular subclass of the common human commensal, B. fragilis, has been associated with inflammatory bowel disease. ETBF colitis is characterized by the activation of Stat3 and a Th17 immune response in the colonic mucosa. This study was designed to investigate the time course and cellular distribution of Stat3 activation in ETBF-colonized mice. Methods: C57BL/6 wild-type, C57BL/6 Stat3ΔIEC, or Rag-1 mice were inoculated with saline, nontoxigenic B. fragilis or ETBF. Histologic diagnosis and mucosal Stat activation (immunohistochemistry, Western blot, and/or electrophorectic mobility shift assay) were evaluated over time (6–24 h, 1–7 d, and 1–18 mo after inoculation). Mucosal permeability was evaluated at 16 hours, 1 day, and 3 days. Mucosal immune responses were evaluated at 1 week, and 12 and 18 months. Results: ETBF induced rapid-onset colitis that persisted for up to 1 year. Stat3 activation (pStat3) was noted in the mucosal immune cells within 16 hours, with colonic epithelial cell activation evident at 24 hours after inoculation. ETBF-induced increased mucosal permeability was first observed at 24 hours after inoculation, after which the initial immune cell pStat3 activation was noted. Immune cell pStat3 was present in the absence of epithelial pStat3 (C57BL/6 Stat3ΔIEC ). Epithelial pStat3 was present in the absence of T and B cells (Rag-1 mice). pStat3 persisted in the epithelial and immune cells for 1 year, characterized by isolated pStat3-positive cell clusters, with varying intensity distributed through the proximal and distal colon. Similarly, mucosal Th17 immune responses persisted for up to 1 year. Loss of fecal ETBF colonization was associated with the loss of mucosal pStat3 and Th17 immune responses. Conclusions: ETBF rapidly induces immune cell pStat3, which is independent of epithelial pStat3. This occurs before ETBF-induced mucosal permeability, suggesting that ETBF, likely through B. fragilis toxin and its action on the colonic epithelial cell, triggers mucosal immune cell Stat3 activation. Peak mucosal Stat3 activation (immune and epithelial cells) occurs subsequently when other colonic bacteria may contribute to the ETBF-initiated immune response due to barrier dysfunction. ETBF induces long-lived, focal colonic Stat3 activation and Th17 immune responses dependent on the ongoing ETBF colonization. Further study is needed to evaluate the early mucosal signaling events, resulting in epithelial Stat3 activation and the sequelae of long-term colonic Stat3 activation.